REVISITING CHINA'S DEVELOPMENTAL STATE: LESSONS FOR AFRICA (The Strategic Review for Southern Africa, 2020)
Prominent development institutions and researchers have documented the ascendance of China in the global political economy and mainly explored how the global balance of power is affected by China's growing economic expansion. Political economists have argued that it is part of the generic economic power shift from the global north to south whilst security studies place emphasis on Chinese national geopolitical interests in several regions. This article discusses what lessons can be drawn from China's developmental state experience and how these can inform Sub-Saharan African developmental strategies. We argue that China's rise has been driven by both market and non-market institutions and show how peculiar contextual historical and socio-political factors have been integral to building the Chinese developmental state. This demonstrates the importance of building effective state institutions to support sustainable economic growth and human development. We highlight the principles shaping institutional mechanisms relating to the rapid economic growth and argue that African governments should apply these in their attempts to rebuild state capacity. However, we also point out that negative trends such as authoritarianism and persistent inequality should not be replicated. Rather, Sub-Saharan Africa should build democratic developmental states characterised by pro-poor sustainable inclusive growth.